The Influence of Competence and Training on the Performance of Family Planning Extension Workers through Job Satisfaction as an Intervening Variable - Riyan Priyosusilo; Tri Adji Pramono (Proceeding of The International Conference on Business and Economics, 2026)
This study aims to analyze the effect of competency synergy and training on performance with job satisfaction both at the Department of Women's Empowerment and Child Protection and Population Control and Family Planning of Pekalongan Regency directly and indirectly. The population used is the Department of Women's Empowerment and Child Protection and Population Control and Family Planning of Pekalongan Regency 160 people, with a sampling technique using the Slovin formula totaling 114 respondents. The data collection method was carried out by means of a questionnaire, the analysis technique used was PLS (Partial Least Square). The results of the study showed that competency synergy had a positive and significant effect on performance optimization and training had a positive and significant effect on performance optimization. Competency synergy had a positive and significant effect on job satisfaction, training had a positive and significant effect on job satisfaction, job satisfaction had a positive and significant effect on performance optimization. And job satisfaction can intervene the effect of competency synergy on performance optimization and job satisfaction can intervene the effect of technology utilization on performance optimization